Analisis Pendapatan Usahatani Tanaman Pala Di Kelurahan Kareko Kecamatan Lembeh Utara Kota Bitung Utara - Manope, Eldiana Prisilia; Kapantow, Gene Henfried Meyer; Montolalu, Maya Hendrietta (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the income of nutmeg farming in Kareko Village, North Lembeh District, Bitung City. This research lasted for 3 (three) months, namely May to July 2023 from the preparation stage, to the preparation of research results. The research was conducted in Kareko Village, North Lembeh District, Bitung City. The data collection method used was the survey method. Data were collected in the form of primary data and secondary data. Primary data were obtained from survey results and direct interviews with farmers based on question data that had been prepared and secondary data were obtained from relevant agencies related to this study. The sampling method used was purposive sampling, respondents were selected as many as 20 respondents. Data analysis used in this research is descriptive analysis using tables to know the amount of income earned by farmers. The results of research on nutmeg farming in Kareko Village, North Lembeh District, Bitung City can be concluded that the average revenue of IDR7,248,500 and production costs of IDR2,016,000 obtained an average income of IDR5,110,475, so the farming carried out provides income for farmers so it is feasible to develop.